Website-based Collection Inventory Information System Design at Wayang Sendang Mas Banyumas Museum - Prasuteja, Soni Gunawan; Wibowo, Adhi; Racma, Dhany Faizal; Widiastuti, Rosalina Yani; Suyudi, Suyudi (Journal of Intelligent Systems and Information Technology, 2024)
The Wayang Sendang Mas Banyumas Museum has 1011 collections that will continue to grow over time. With so many collections, there are obstacles in the inventory process, especially in the collection data reporting section. The current inventory process is still carried out semi-manually, using Microsoft Excel and Microsoft Word, resulting in less time efficiency in the process of making collection data reports. The purpose of this research is to prove that the existence of a Website-Based Collection Inventory Information System at the Wayang Sendang Mas Banyumas Museum can increase efficiency in the process of making museum collection data reports. This system was built with the help of the CodeIgniter Framework, the programming language used is PHP, and the system development method uses the prototype method, which is a technique for collecting specific information about the information needs needed by users quickly. The system that has been built is tested with several tests, including system testing using black-box testing and white-box testing methods; hypothesis testing using paired sample t-test; and testing the benefits using the ISO 25010 test model. The results of the benefits testing obtained a percentage of answers based on the criteria agree and strongly agree by 100% on the Performance Efficiency aspect. Based on the results of the benefits testing, it can be concluded that the system that has been built has succeeded in helping the museum in increasing efficiency in the process of making museum collection data reports.